Classrooms as ‘safe houses’? The ethical and emotional implications of digital storytelling in a university writing classroom - Stewart, Kristian D (Critical Studies in Teaching and Learning, 2023)
This paper reports the findings of a digital storytelling praxis within a higher education classroom located outside of Metro Detroit in the United States. Drawing on Zembylas’s (2006, 2008) scholarship on emotion in the production of knowledge and the teacher’s role, adjacent to literature surrounding personal writing and safe houses for learning, an investigation of student perceptions of digital storytelling within a writing classroom took place during the 2016and 2017 academic years. Data highlights the students’ interest for the emotionally-driven course content digital storytelling encourages, as it taught students how to insert genre conventions into their own writing. Digital storytelling, according to the students, also supplied a means for students to develop relationships with their peers as many students felt isolated on this largely commuter campus. Students additionally viewed the curriculum as promoting ‘real world’ skills they could transfer outside of the classroom and into their lives. However, to craft digital stories, data revealed how students turned toward sharing personal (and or traumatic) narratives. This can be problematic in terms of emotional safety if students are made to feel they must leverage emotions for grades and are then forced to broadcast their digital stories in a public forum. To lessen these concerns, strategies for implementing digital storytelling into the curriculum are provided. Lastly, the author concludes that educating students within a Trump presidency requires a different pedagogical approach. Assignments such as digital storytelling that merge the scholarly and the personal, alongside nurturing empathy, open dialogue, and building relationships might offer a direction forward.